HUBUNGAN PERLAKUAN BODY SHAMING DENGAN CITRA DIRI MAHASISWA [THE RELATIONSHIP BETWEEN BODY SHAMING BEHAVIOR AND STUDENTS SELF IMAGE] - Dwi Sri Widiyani; Desinta Aditiya Rosanda; Tonny F Cardella; Maria V Ayu Florensa; Mega Tri Anggraini Setia Ningsih (Universitas Pelita Harapan, 2021)
Body shaming is an unpleasant experience experienced by individuals when it is seen as something negative by others from their body shape. The impact of body shaming can result in victims becoming insecure and less confident. Research objective to determine the relationship between body shaming behavior and student selfimage. Research method is quantitative descriptive correlational and cross sectional approac. This research was conducted in April-May 2020. The statistical test used was the Somersd test. Instrument used a body shaming questionnaire and a self-image questionnaire that had been tested by VR with a cronbach alpha value of 0.795 for body shaming treatment and 0.811 for self-image. Population was 176 samples which were counted using purposive sampling method. Results of univariate analysis showed that 85.2% of students received low body shaming treatment and 56.2% of students had a negative self-image, statistical tests obtained p value 0.015 <α 0.05 with somers'd value -0.257, which means that there is a significant relationship between treatments. body shaming with student self-image with negative correlation direction. Suggestions for educational institutions to continue to instill good tolerance values in students and this research are expected to become library reading materials in developing science in the health sector.BAHASA INDONESIA Perlakuan body shaming adalah pengalaman tidak menyenangkan yang dialami individu ketika dipandang sebagai sesuatu yang negatif oleh orang lain dari bentuk tubuhnya. Dampak dari perlakuan body shaming dapat mengakibatkan korban menjadi minder dan kurang percaya diri. Tujuan penelitian ini untuk mengetahui hubungan perlakuan body shaming dengan citra diri mahasiswa. Metode penelitian ini yaitu kuantitatif deskripif korelasional dan pendekatan cross sectional. Penelitian ini dilakukan pada bulan April-Mei 2020. Uji statistik yang digunakan adalah uji somers’d. Instrumen penelitian menggunakan kuesioner perlakuan body shaming dan kuesioner citra diri yang telah dilakukan uji VR dengan nilai cronbach alpha 0,795 untuk perlakuan body shaming dan 0,811 untuk citra diri. Sampel yang digunakan sebanyak 176 sampel yang dihitung menggunakan metode purposive sampling. Hasil analisa univariat menunjukkan 85,2% mahasiswa menerima perlakuan body shaming rendah dan 56,2% mahasiswa memiliki citra diri negatif, uji statistik didapatkan p value 0,015 < α 0,05 dengan nilai somers’d -0,257 berarti terdapat hubungan yang bermakna antara perlakuan body shaming dengan citra diri mahasiswa dengan arah korelasi negatif. Saran bagi institusi pendidikan agar terus menanamkan nilai-nilai toleransi yang baik kepada mahasiswa dan penelitian ini diharapkan dapat menjadi bahan bacaan perpustakaan dalam mengembangkan ilmu pengetahuan dalam bidang kesehatan.